CABAC-based selective encryption for HEVC using RC6 in different operation modes - Sallam, Ahmed I.; El-Rabaie, El-Sayed M.; Faragallah, Osama S. (Multimedia tools and applications, 2018)
This paper proposes a selective encryption (SE) algorithm for the almost recently video compressing technique that is called High-Efficiency Video Coding (HEVC). The improvement of our HEVC SE algorithm is to secure real-time HEVC streaming using low computational overhead, same bit rate and ensuring the video format compliance. This contribution is achieved with low computational RC6 algorithm to encrypt subset of binstrings that is binarized using the bypass binary arithmetic coding mode in the context adaptive binary arithmetic coding (CABAC) process of HEVC. This binstrings subset is the non-zero discrete cosine transform (DCT) coefficients sign bits, motion vector difference (MVD) sign bits, remaining absolute values suffix of DCT, MVD absolute values suffix, Sample adaptive offset (SAO) sign bit, residual size, reference picture index and the delta Quantization Parameter (QP). Also, this paper investigates the performance evaluation of using the RC6 with its operation modes within the proposed HEVC CABAC SE. This investigation is done for choosing the best operation mode for RC6 to be suitable for being used in the HEVC real-time application. The security analysis like histogram analysis, correlation coefficients test and key sensitivity test are presented to make sure the protection of HEVC CABAC SE algorithm against brute force and statistical attacks. The performance analysis results prove that the HEVC CABAC SE is highly secure and can be used in real-time HEVC applications.